In vitro antioxidant and antimicrobial effects of Streblus asper: An ethnomedicinal plant of Assam, India - Boruah, Gouranga; Borah, Sudarshana; Laskar, Tanjima Tarique; Arora, Monica; Pathak, Kamla (Edelweiss Applied Science and Technology, 2025)
Streblus asper Lour, a member of the Moraceae family, is a widely recognized ethnomedicinal plant in India, the Philippines, Malaysia, and Thailand. It is valued for its antimicrobial, antioxidant, anti-inflammatory, and antidiabetic properties. This study investigates the in vitro antioxidant and antimicrobial activities of S. asper hydroalcoholic extract, validating its traditional use among local communities in Assam. Plant samples, collected from Lakhimpur, Assam, and authenticated by the Botanical Survey of India, underwent extensive phytochemical screening, revealing the presence of cardiac glycosides, triterpenoids, phytosterols, coumarins, and anthocyanins. The antioxidant activity, assessed via the DPPH free radical scavenging method, yielded an IC50 value of 263.84±0.14 µg/ml, indicating significant radical scavenging potential. Antimicrobial efficacy was evaluated using the agar well diffusion method against Escherichia coli and Staphylococcus aureus, with a minimum inhibitory concentration of 60 µl and maximum activity at 120 µl, comparable to standard antibiotics such as azithromycin and penicillin G. Physicochemical standardization, including loss on drying, ash values, and extractive values, confirmed the extract's quality. These findings support the ethnomedicinal significance of S. asper, particularly as a dental stick in Assam for preventing oral ailments. The study emphasizes the plant's potential for developing novel therapeutic formulations and highlights the need for further research to explore its pharmacological applications, aiming to integrate it into modern medicine for societal health benefits.